Process improvement software through assessment using CMMI framework / Yaya Sudarya Triana - Triana, Yaya Sudarya (Faculty of Computer and Mathematical Sciences, 2021)
The growth of technology in the field of information today, has caused intense competition among information technology companies, especially in the field of software development. Software development is a very complicated activity, because it is a technological process, which involves social and economic dimensions. Experts working in technical fields such as designers, systems analysts, programmers, testers, and project managers as developers who work to support non-technical interests to build changes in software development can bring positive developments in society. In fact, there are many customers who complain, because the software products made by development are often late, then not in accordance with needs, there are still many bugs, and do not have the appropriate documents, and are difficult to maintain. As a result, the software that has been built cannot be used properly and is considered a failure. For this reason, there is a need for standardization in the development of software created by development, so that customers who will build software can choose developers who have the expected standards, such as Capability Maturity Model Integration (CMMI). This study aims to measure the impact of CMMI levels for PT XYZ. The method used is self-assessment using a questionnaire that was asked to employees of PT XYZ. This assessment is based on a questionnaire were adopted from CMMI. The results obtained from this analysis and measurement are that the company has only reached maturity level 2. In conclusion, this company has not been able to develop a large information system but must continue to improve its performance to be able to increase to a higher level.